Head Injury- A Maxillofacial Surgeon’s Perspective - MURALEE MOHAN CHOONTHAR; ANANTHAN RAGHOTHAMAN; RAJENDRA PRASAD; S PRADEEP; KALPA PANDYA (Journal of Clinical and Diagnostic Research, 2016)
Injuries and violence are one of the leading causes of mortality worldwide. A substantial portion of these injuries involve the maxillofacial region. Among the concomitant injuries, injuries to the head and cervical spine are amongst those that demand due consideration on account of their life threatening behaviour. Studies have shown that facial fractures have a strong association with traumatic brain injury. Knowledge of the types and mechanisms of traumatic brain injury is crucial for their treatment. Many a times, facial fractures tend to distract our attention from more severe and often life threatening injuries. Early diagnosis of these intracranial haemorrhage leads to prompt treatment which is essential to improve the outcome of these patients. An oral and maxillofacial surgeon should be able to suspect and diagnose head injury and also provide adequate initial management.